(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pediatric oncology has a major role in research. This paper discuss about the ethical consequences of physiotherapy care and research in Pediatric Oncology. Empirical ethics is a broad division,grasping, difference in indicatingethics and empirical research. A major Australian tertiary teaching hospital reveals that 65 % of patient presents with specific indication for physiotherapy, in that only12.8% are receiving physiotherapy. Indications includes in physiotherapy care are pain, lymph- oedema, incontinence, respiratory and musculoskeletal Problems also it includes hard to move. Physiotherapy has extensive role inpalliative oncology, it also has large preventative ,educative and supportive roles to play and provides independent and complementary therapies for physical debility and pain. Pain from reflex spasm and contracture are dealt with Physiotherapists. Founded that no reference based on standard of life and quality-adjusted life years in terms of preventing dependance and avoid hospitalisation. Treatment of pediatric oncology often has physically, socially and psychologically demands. Always there must be some ethical reason for all the decision on treatment and care for a patient with cancer. It is a fact that ethics needs not only all the stakeholders to do the right things but also it needs the one who do it in the right way. Research practice has led us to great advances in pediatric oncology and the proportion is greater in children than adults. Obtaining the informed consent and assent was the most important ethical challenges faced during the research.